2015
DOI: 10.1093/icvts/ivv259
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the total pericardial closure using bilateral trap door incision and pericardial cavity intervention on outcomes following coronary artery bypass grafting: a randomized, controlled, parallel-group prospective study

Abstract: Total pericardiorrhaphy with pericardial cavity intervention can be acceptable and favourable in terms of its outcomes, including reducing incidence of postoperative atrial fibrillation, pericardial effusion and length of hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…Of those, 18 were further excluded because they were not pertinent to the design of the meta-analysis or did not meet the explicit inclusion criteria. Nineteen RCTs 11,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] that enrolled 3425 patients eventually were included in the analysis. Patients were divided into 2 groups: those with a posterior pericardial drainage (n ¼ 1723) and control group without (n ¼ 1702).…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Of those, 18 were further excluded because they were not pertinent to the design of the meta-analysis or did not meet the explicit inclusion criteria. Nineteen RCTs 11,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] that enrolled 3425 patients eventually were included in the analysis. Patients were divided into 2 groups: those with a posterior pericardial drainage (n ¼ 1723) and control group without (n ¼ 1702).…”
Section: Study Selectionmentioning
confidence: 99%
“…In the group of patients who received a posterior pericardial drainage, 1447 patients underwent PP 11,[19][20][21][22][23][24][25][26][28][29][30][33][34][35][36][37] ; in 103 patients, a chest tube was placed within the posterior pericardium 27,30 ; 173 patients received both PP and posterior pericardium chest tube. 31,32 On-pump coronary artery bypass grafting (CABG) was the most frequently performed cardiac procedure, 11,19,20,23,25,28,[30][31][32][33][34][35][36] followed by combined CABG and/or valve replacement. 21,22,24,37 Two studies reported on patients undergoing valve replacement and/or ascending aorta surgery 26,27 and another on patients who received offpump CABG alone.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The corresponding event rates were 0.42% (6/1431) versus 4.95% (70/1413). (18) 2006 0 50 1 50 0.33 Eryilmaz et al (19) 2006 2 70 6 70 0.31 Bakhshandeh et al (20) 2009 0 205 10 205 0.05 Kaygin et al (24) 2011 0 213 7 212 0.06 Zhao et al (25) 2014 3 228 13 230 0.22 Kaya et al (26) 2014 0 63 4 33 0.05 Fawzy et al (27) 2015 0 100 3 100 0.14 Kaya et al (29) 2015 1 70 1 72 1.03 Kaya et al (30) 2016 0 103 4 107 0.11 total (95% CI) 1156 1138 0.12…”
Section: Primary Endpointmentioning
confidence: 99%